SOSIALISASI DAN PENGUKURAN FORWAD HEAD POSTURE (FHP) PADA REMAJA DI SMAN 3 BANJARMASIN - Dadan Prayogo; Akhmad Ridhani; Utomo Wiaksono; Bernadus Sadu; Rizky Ridhayanti; Juliani Saputri; Uswatun Hasanah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
One of the postures on the neck that is not ergonomic is the Forward head posture (FHP), which is the position of the head in front of the shoulders. The disorder is caused by a static bending neck position that is too long. In addition to position, static activity with a long duration and lack of support on the arms and fingers when using a smartphone results in a continuous static load on the neck muscles so that there is a risk of forward head posture (FHP). The purpose of this community service is to socialize and find out the measurement of forward head posture (FHP) in adolescents. This activity was carried out by filling out pre-tests, post-tests, and measurements as well as socializing the presentation of material about forward head posture (FHP) to students. Forward head posture (FHP) was measured using a goniometer with marker C7 and tragus then measured at that angle. From the results of the forward head posture (FHP) measurement using a goniometer, the results were obtained: 12 students of normal FHP, 12 students of medium FHP, and 2 students of heavy FHP.